2017
DOI: 10.1002/2016jc012511
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional pathways of water masses in the South China Sea: A modeling study

Abstract: We conduct a numerical Eulerian analysis on the Lagrangian characteristics of South China Sea (SCS) water masses. This is the first study to investigate the water pathway and residence time in response to time‐dependent, three‐dimensional basin circulation in the SCS. The circulation of the SCS is largely determined by westward intrusions of the northwestern Pacific waters in the upper layer (0–750 m) and deep layer (>1500 m), and by an eastward extrusion in the intermediate layer (750–1500 m) through Luzon St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…While it is close to the δ 15 N of N 2 fixer biomass and the DON they produce (Carpenter et al, 1997;Macko et al, 1987;McRose et al, 2019;Minagawa & Wada, 1986;Zerkle et al, 2008), we know of no reason to expect N 2 fixers to dominate net DON production in this region. The SCS has relatively strong vertical exchange and net upwelling, with both monsoonal seasons hosting conditions that encourage vertical fluxes (Liu & Gan, 2017). This results in high vertical nitrate flux to the euphotic zone on an annual basis, which dominates new production (Liu et al, 2010;.…”
Section: 1029/2020gb006551mentioning
confidence: 99%
“…While it is close to the δ 15 N of N 2 fixer biomass and the DON they produce (Carpenter et al, 1997;Macko et al, 1987;McRose et al, 2019;Minagawa & Wada, 1986;Zerkle et al, 2008), we know of no reason to expect N 2 fixers to dominate net DON production in this region. The SCS has relatively strong vertical exchange and net upwelling, with both monsoonal seasons hosting conditions that encourage vertical fluxes (Liu & Gan, 2017). This results in high vertical nitrate flux to the euphotic zone on an annual basis, which dominates new production (Liu et al, 2010;.…”
Section: 1029/2020gb006551mentioning
confidence: 99%
“…Positive N* and high ambient O 2 in the deep water does not support N 2 O production by local denitrification in the water column. However, the deep water in the study region originates partly from the western North Pacific waters (Kuroshio; Liu & Gan, 2017), which may carry an isotopic signal from a remote region with water column denitrification, that is, the ETNP. In these waters, N 2 O may be produced predominantly by denitrification with partial reduction in the oxygen deficient zone (Fujii et al, 2013;Yamagishi et al, 2007).…”
Section: 1029/2019jc014947mentioning
confidence: 99%
“…As an ocean-dominated marginal sea, the SCS is characterized by intensive interactions with the West Philippine Sea (WPS) via the Luzon Strait (Figure 1). The Kuroshio usually intrudes westward into the upper layer (<750 m) and deep layer (>1,500 m) of the SCS, while the intermediate layer (750-1,500 m) extrudes eastward through the Luzon Strait (Liu & Gan, 2017). Overall, the SCS basin is oligotrophic Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Importantly, the influence of intruded Kuroshio on the seawater chemistry in the nSCS can sustain for years. Liu and Gan (2017) indicated that the intruded Kuroshio in the upper layer had a residence time of about 3 years before subducting into deeper layers or flowing out of the SCS. Restated, the intruded Kuroshio could have inter-annual influences on the biogeochemical cycles in the SCS.…”
Section: Climatic Oscillation Of Intrusion Patterns and Its Implicationsmentioning
confidence: 99%